Nontrivial solutions for a fractional advection dispersion equation in anomalous diffusion - Zhang, Xinguang; Liu, Lishan; Wu, Yong Hong; Wiwatanapataphee, Benchawan (Elsevier, 2017)
© 2016 Elsevier LtdIn this paper, we consider the existence of nontrivial solutions for a class of fractional advection–dispersion equations. A new existence result is established by introducing a suitable fractional derivative Sobolev space and using the critical point theorem.